Оптимізація пайплайну цифрового скульптингу в ZBrush - Логвиненко, Д. В.; Петренко, І. І. (ХНУРЕ, 2025)
ZBrush is one of the leading digital sculpting software solutions widely used in the creation of 3D models for the film, game development, and virtual reality industries. This article explores the complete pipeline of working with ZBrush, from initial blocking to final rendering. The research highlights key tools and techniques used at each stage of the pipeline, emphasizing the importance of automated features such as DynaMesh, ZRemesher, and UV Master. Particular attention is given to the integration of ZBrush with other software packages and the optimization of the workflow to improve the quality and efficiency of 3D model creation. The results of this study can serve as a guideline for both novice and experienced 3D artists looking to enhance their skills and streamline their workflow.
Keywords: ZBrush; 3D models for the film